Effect of intracanal diode laser application and low-level laser therapy on CGRP change - Hakan Arslan; Serhat Köseoğlu; Ezgi Doğanay Yildiz; Taner Arabaci; Levent Savran; Dursun Anıl Yildiz; Gözde Veyisoğlu (Sociedade Brasileira de Pesquisa Odontológica, 2019)
Abstract: The aim of this study was to investigate the effect of a placebo, intracanal diode laser application, and low-level laser therapy (LLLT) on the change of the total amount of calcitonin gene-related peptide (CGRP) in the gingival crevicular fluid (GCF) (split-mouth study design). GCF sampling was performed on a contralateral tooth and experimental tooth (root canal-treated tooth) of thirty-nine patients. The patients were divided into three groups (n = 13), as follows: placebo (mock laser application), intracanal laser application, and LLLT. GCF sampling was repeated at the same sites (experimental and control teeth) one week after root canal treatment. The data were analyzed using the Pearson's correlation analysis and the independent-samples t-tests (p=0.05). In the placebo group, the total CGRP level changes in the GCF before and after treatment was significantly higher for experimental teeth than for control teeth (p<0.05). However, there was no significant difference between experimental and control teeth in the intracanal laser application and LLLT groups (p > 0.05). Intracanal laser application and low-level laser therapy have immunomodulation effects linked to the modulation of the total amount of CGRP in the GCF.